2015
DOI: 10.1007/s11846-015-0170-z
|View full text |Cite
|
Sign up to set email alerts
|

Is trust in leadership a mediator between transformational leadership and in-role performance among small-scale factory workers?

Abstract: Globalization and the transformation of the organizational scene are increasing the pressure and threshold for employees to constantly perform maximum output. As such, the measure of success for many organizations is determined by their productivity level. Therefore, we believe that the leadership style adopted by the leader and the level of trust subordinates have in such a leader may be salient in determining the level of in-role performance of the subordinates in question. This study therefore tries to shed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…Trust benefits performance particularly under vision-based leadership (Arnold, Barling, & Kelloway, 2001; Y.-F. Yang, 2014), but whether trust actually mediates the performance-enhancing effect of visionary leadership still needs clarifying. Some researchers (Casimir, Waldman, Bartram, & Yang, 2006; Y.-F. Yang, 2014) provide supportive evidence, whereas others report that trust does not mediate individual performance beyond the effects of transformational leadership itself (Ugwu, Enwereuzor, & Orji, 2016). Trust also plays a crucial performance-enhancing role under organic or shared leadership (Drescher et al, 2014), including as a mediator of job satisfaction (Jain, 2016).…”
Section: Mediating Variables Interactions and Hypothesesmentioning
confidence: 99%
“…Trust benefits performance particularly under vision-based leadership (Arnold, Barling, & Kelloway, 2001; Y.-F. Yang, 2014), but whether trust actually mediates the performance-enhancing effect of visionary leadership still needs clarifying. Some researchers (Casimir, Waldman, Bartram, & Yang, 2006; Y.-F. Yang, 2014) provide supportive evidence, whereas others report that trust does not mediate individual performance beyond the effects of transformational leadership itself (Ugwu, Enwereuzor, & Orji, 2016). Trust also plays a crucial performance-enhancing role under organic or shared leadership (Drescher et al, 2014), including as a mediator of job satisfaction (Jain, 2016).…”
Section: Mediating Variables Interactions and Hypothesesmentioning
confidence: 99%
“…Soane et al (2015) suggest that the transformational leadership style has a positive impact on employees performance. This statement is similar to Ugwu et al (2016), that transformational leadership provides positive predictions in role performance. Transformational leadership has a significant influence on work motivation, and work motivation has a positive effect on employees performance (Syaifuddin, 2016).…”
Section: Introduction 11 Research Backgroundsupporting
confidence: 80%
“…However, some studies also found non-significant effects (e.g., Atuahene-Gima & Li, 2002;Ugwu et al, 2016). Specific sample characteristics (such as a non-Western cultural setting) may explain the non-significant effect on the relationship (Ugwu et al, 2016).…”
Section: Trust In Leadership and Performancementioning
confidence: 98%
“…However, some studies also found non-significant effects (e.g., Atuahene-Gima & Li, 2002;Ugwu et al, 2016). Specific sample characteristics (such as a non-Western cultural setting) may explain the non-significant effect on the relationship (Ugwu et al, 2016). It has been argued that in some non-Western cultures extrinsic motivators (e.g., good pay, retirement benefits) could play a more significant role in motivating employees than trust in the leader alone (Ugwu et al, 2016).…”
Section: Trust In Leadership and Performancementioning
confidence: 99%
See 1 more Smart Citation